Future liver remnant portal or hepatic vein reconstruction at stage I of ALPPS—How far can we push the boundaries?. Issue 4 (16th July 2019) - Schlegel, Andrea; Sakuraoka, Yuhki; Kalisvaart, Marit; Coldham, Chris; Isaac, John; Muiesan, Paolo
Abstract: Preservation of the future liver remnant (FLR) vascular integrity has always been considered crucial to achieving successful liver growths after major hepatectomies. Most surgeons appeared therefore reluctant to combine stage I of associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) with vascular reconstructions. Here we describe a case series, where we combine parenchymal transection and venous in‐ or outflow reconstruction of the FLR at stage I of ALPPS. In addition, the cold flush of the FLR or delayed portal vein embolization is applied in selected cases.